PERMAINAN TRADISIONAL DALAM BUDAYA DAN PENINGKATAN INTERAKSI SOSIAL ANAK - Ratu Husna Aulia; Nabila Ariyanda; Zakia Aulia Zikra; Zahratul Alya Anwar; Lexa Putri Amanda; Tiara Syahfitri; Aufa Nur Asyifa; Yuhelsa Marsanda (CV. Denasya Smart Publisher, 2025)
This research aims to evaluate the impact of traditional games on the development of children's social interaction skills, highlighting its relevance amidst the shift in children's interests from traditional to digital games and the ongoing challenges of conventional mathematics education. Through a comprehensive literature review approach, this article analyzes the effectiveness of traditional games such as congklak, cak bur, and engklek in supporting cognitive, motor, and socio-emotional development in early childhood. The research findings indicate that traditional games significantly enhance social interaction skills, as evidenced by the effectiveness of cak bur in improving social interaction among kindergarten students and the role of congklak in the socio-emotional development of young children.